A GENERALIZED MULTISOURCE SYMMETRICAL MULTILEVEL INVERTER WITH REDUCED SWITCHES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper proposes a generalized multisource symmetrical multilevel inverter with reduced switches. The proposed topology uses fewer switches, thereby minimizing switching losses and improving system efficiency. The salient features of this topology are the elimination of diodes and capacitors, a reduced number of switches, the ability to expand the circuit to achieve as many levels as needed, reduced total standing voltage (TSV), reduced cost, and lower Total Harmonic Distortion (THD). The phase-disposition level-shifted pulse-width modulation technique is used, and logic gates are employed to generate triggering pulses. The proposed topology is simulated in MATLAB/Simulink for 11 levels, with 5 DC sources and nine switches. The performance analysis for the resistive and inductive loads was performed. I have also provided a detailed comparison with other recent research works to demonstrate the effectiveness of the proposed system. The proposed topology is also realized using the hardware for an 11-level output.
Keywords: Multilevel inverters; Multisource; Phase disposition; Level shifted; Pulse width modulation; Symmetrical; Total harmonic distortion